Omophorus (Sinomophorus) wallacei: a new weevil from Borneo highlights the enigmatic Ethiopian-Oriental disjunct distribution (Coleoptera, Curculionidae, Molytinae) - Tseng, Wei-Zhe; Hsiao, Yun; Hsu, Chen-Fu (Zootaxa, 2018)
In the present study we describe a new species of the genus Omophorus, O. (Sinomophorus) wallacei sp. nov., from Malaysian Borneo. Photographs of habitus and genitalia, a distribution map, and a key for the identification of Omophorus species are included. The definition of the subgenus Sinomophorus is revised and several new diagnostic characters are added. This is the first documented occurrence of Omophorus in Borneo, highlighting its potential diversity in the Oriental region and providing additional evidence of Ethiopian-Oriental disjunction within this genus.